Improvement of prediction of oil displacement efficiency during waterflooding due to detailing of lithological distribution - Martus, Olena; Cvetkovic, Branimir; Mykhailovska, Olena; Yaholnyk, Andrii; Liashenko, Anna (Technology audit and production reserves, 2025)
The object of research is the process of oil displacement during waterflooding. The research aims to develop and substantiate a methodology that improves the reliability of predicting oil displacement efficiency during waterflooding. For this purpose, the classical Buckley-Leverett method and the State Standard of Ukraine method for calculating the oil displacement efficiency during waterflooding were extended by integrating lithological data, which allows considering the influence of geological characteristics on the process of oil displacement by water. The developed methodology for improving the reliability of oil displacement efficiency prediction encompasses the identification of lithofacies and the determination of core and fluid sample properties. Subsequently, the representative elementary volume (REV) is ascertained for each facies. Based on this, the irreducible water saturation and irreducible oil saturation are calculated. Relative permeability curves are then constructed for each facies. The Buckley-Leverett equation is applied, and fractional flow curves are generated. The data is integrated into a three-dimensional reservoir model, with facies volumes determined using the kriging method. Finally, the averaged oil displacement efficiency is calculated. A comparative analysis of the reliability of methods, with and without lithological subdivision, was conducted by constructing an experimental histogram and a normal distribution plot, considering or disregarding lithological distribution, respectively. For the comparative analysis, this research generates one hundred reservoir realizations, both with and without lithological subdivision, using the Sequential Indicator Simulation tool. It was established that the use of lithological data in the calculations of the Buckley-Leverett method, with consideration of the lithological factor, allows a reduction in the scatter of predicted values by 11% in comparison with a similar method without consideration of the lithological factor. The originality of the research lies in integrating lithological distribution into the Buckley-Leverett method and the State Standard of Ukraine method of calculating the oil displacement efficiency during waterflooding, which significantly improves the predictive results. The proposed approach allows considering the lithological factor at the level of analytical formulas when calculating the two methods.